2022
DOI: 10.3233/jpd-223447
|View full text |Cite
|
Sign up to set email alerts
|

Boxing with and without Kicking Techniques for People with Parkinson’s Disease: An Explorative Pilot Randomized Controlled Trial

Abstract: Background: People with Parkinson’s disease (PD) benefit from boxing exercise. Adding kicking variations to the boxing may provide additional benefit to improve balance. However, the benefits and adherence to such trainings is unknown. Objective: To explore the feasibility, safety, and benefits on balance of boxing training combined with kicking techniques in comparison to boxing without kicking in PD. Methods: Participants were randomized to group-based boxing training with kicking techniques (BK) or to group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(37 citation statements)
references
References 55 publications
1
36
0
Order By: Relevance
“…Sangarapillai et al 8 examined the utility of boxing training compared to a sensory exercise program and reported similar adherence (98%) and retention (100%) rates to the present study. Domingos et al 10 investigated boxing training with and without kicking exercises and also noted high adherence (85%). This study, however, reported lower retention (86%) than the present study and work by Sangarapillai et al 8 It is noteworthy that FIGHT‐PD and work by Sangarapillai et al 8 included high‐intensity boxing training sequences and reported no serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sangarapillai et al 8 examined the utility of boxing training compared to a sensory exercise program and reported similar adherence (98%) and retention (100%) rates to the present study. Domingos et al 10 investigated boxing training with and without kicking exercises and also noted high adherence (85%). This study, however, reported lower retention (86%) than the present study and work by Sangarapillai et al 8 It is noteworthy that FIGHT‐PD and work by Sangarapillai et al 8 included high‐intensity boxing training sequences and reported no serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Domingos et al 10 provided greater detail, describing the composition and specific exercises prescribed in a boxing training program with and without kicking. This study did not detail the intensity of training sessions with rates of perceived exertion (RPE) or heart rate (HR) monitoring and did not report compliance.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation was performed separately by the two researchers (T.G) and (P.D), and disagreements between the assessors were discussed and resolved through consensus. The three included studies were of a high methodological quality, scoring 7/10 [11,46,47], and the related scores are presented in Table 2. -1 1 1 0 0 1 0 1 1 1 7/10 Domingos et al [47] -1 0 1 0 0 1 1 1 1 1 7/10 Sangarapillai et al [11] -1 0 1 0 0 1 1 1 1 1 7/10…”
Section: Methodological Qualitymentioning
confidence: 99%
“…The three included studies were of a high methodological quality, scoring 7/10 [11,46,47], and the related scores are presented in Table 2. -1 1 1 0 0 1 0 1 1 1 7/10 Domingos et al [47] -1 0 1 0 0 1 1 1 1 1 7/10 Sangarapillai et al [11] -1 0 1 0 0 1 1 1 1 1 7/10…”
Section: Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation